Contextual factors influencing performance in the new synchronous online assessment among IIUM preclinical medical students - Wan Omar, Wan Fatein Nabeila; Mohd Zainudin, Maizura; Hamzah, Hairul Aini; Abdul Rahim, Roslina; Khaing, Aye Thi; Ismail, Soraya; Ismawi, Hidayatul Radziah; Mat Harun, Noraihan; Mohamed Bakrim, Norbaiyah (2021)
This poster was submitted to Putra Innocreative Carnival in Teaching and Learning 2020 that was held virtually from 22-28th October 2020. This presentation won the Bronze Award.